2013
DOI: 10.3390/molecules18089179
|View full text |Cite
|
Sign up to set email alerts
|

Syzygium jambos and Solanum guaraniticum Show Similar Antioxidant Properties but Induce Different Enzymatic Activities in the Brain of Rats

Abstract: Syzygium jambos and Solanum guaraniticum are both employed in Brazil as medicinal plants, even though their potential toxicity is not well established and they are frequently misused. The aim of this study was investigate the effect of the aqueous leaf extracts of both plants on δ-aminolevulinate dehydratase (δ-ALA-D) and acetylcholinesterase (AChE) activities and the antioxidant action against oxidative damage induced by sodium nitroprusside in rats, using in vitro assays. In addition, the presence of gallic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
(58 reference statements)
2
19
0
2
Order By: Relevance
“…Recent in vitro studies have demonstrated that Solanum guaraniticum leaf extract displays radical scavenger activity, and protective effects against oxidative injury in cells and tissues (Bonfanti et al, 2013(Bonfanti et al, , 2014Zadra et al, 2012). The Brazilian Pharmacopoeia describes only S. paniculatum L. as the true jurubeba (Corrêa, 1984), yet interchangeable use of these two species by folk medicine is common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vitro studies have demonstrated that Solanum guaraniticum leaf extract displays radical scavenger activity, and protective effects against oxidative injury in cells and tissues (Bonfanti et al, 2013(Bonfanti et al, , 2014Zadra et al, 2012). The Brazilian Pharmacopoeia describes only S. paniculatum L. as the true jurubeba (Corrêa, 1984), yet interchangeable use of these two species by folk medicine is common.…”
Section: Introductionmentioning
confidence: 99%
“…The heme pathway enzyme deltaaminolevulinate dehydratase (δ-ALA-D, EC 4.2.1.24) presents high sensitivity to pro-oxidant situations, and to impairment of metabolic processes, thus being used to evaluate toxicity as well (Nogueira et al, 2003;Souza et al, 2009). Previous studies by our group have already demonstrated the inhibitory in vitro effects of S. guaraniticum extract on erythrocyte and brain δ-ALA-D, suggesting possible extract caused hematological and central nervous systems impairments (Bonfanti et al, 2013(Bonfanti et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This research was intended to verify the content and antioxidant activity of S. jambos leaves in each developmental stages of leaves. This is to follow up the previous studies about Malabar plum leaves without examining the stages of leaves development (Islam et al, 2012;Bonfanti et al, 2013, andDhanabalan et al, 2014). The findings show that the old leaf stage has the highest content and antioxidant activity (ascorbic acid and phenol) compared to the mature and young leaves stage.…”
Section: Resultsmentioning
confidence: 92%
“…Syzygium jambos belongs to the Myrtaceae family. It is a typical tropical plant which contains many secondary metabolite compounds (Mohanty & Cock, 2010), such as ascorbic acid, phenols, caffeine, kaempferol, gallic acid, rutin, chlorogenic acid, quercetin, and flavonoids (Bonfanti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation